Review of synergy between machine learning and first principles models for asset integrity management - Cai, Tianxing; Fang, Jian; Daida, Sharath; Lou, Helen H. (Frontiers in Chemical Engineering, 2023)
The chemical process industry (CPI) accumulated a rich data asset through industrial 4.0. There is a strong drive to develop and utilize effective approaches for process performance prediction and improvement, process control, sensor development, asset management, etc. The synergy between machine learning and first principles models can bring new insights and add tremendous value to the CPI. This paper reviews various applications of the synergies towards asset integrity management. An overview of some related commercial software packages are also provided.